A systematic study of determination and validation of finasteride impurities using liquid chromatography - CÜCÜ, AYŞEN (ELSEVIER, 2020)
Pharmaceutical use of finasteride (Dilaprost (R)) has been well documents in the peer-reviewed literature; however, the presence of trace amounts of related substances (impurities) in finasteride may influence the tharapeutic efficacy and safely. Due to limited information available, the objective of this study was to develop a quantification method for the three impurities of finasteride using high performance liquid chromatography (HPLC) with an ultraviolet (UV) detector. The compounds (impurities) of finasteride that are registered with the European Pharmacopeia, which we sought to validate are: -N-(1,1-dimethylethyl)-3-oxo-4-aza-5 alpha-androstane-17 beta-carboxa mide (impurity A), methyl 3-oxo-4-aza-5 alpha-androst-1-ene-17 beta-carboxylate (impurity B), and -N-(1,1-dimehylethyl)-3-oxo-4-azaandrosta-1,5-diene-17 beta-carboxamide (impurity C). Analyses were performed using a Nova Pac C-18 column for HPLC with isocratic elution. Detection was carried out at 210 nm, the concentration of the three impurities was in the range was 1.5-4.5 mu g mL(-1) at ambient temperature with a mobile phase of water + acetonitrile + tetrahydrofuran (80:10:10, v/v/v) and the flow rate was 2.0 mL min(-1). The recoveries were: 101.35 +/- 0.62% (impurity A), 101.60 +/- 2.66% (impurity B) and 101.97 +/- 2.05% (impurity C). Validation of the method yielded fairly good results as it relates to the precision and accuracy. It is, therefore, concluded that the method would be suitable for not only the separation and determination of processed impurities to monitor the reactions, but also for the quality assurance of finasteride and its related substances. (C) 2019 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Finasteride; Impurities; Validation; Analytical; HPLC; Pharmaceutical use; HUMAN PLASMA; RAT